Agri-Nanotechnology and Tree Nanobionics: Augmentation in Crop Yield, Biosafety, and Biomass Accumulation - Abbas, Manzar; Yan, Kuan; Li, Jia; Zafar, Sara; Hasnain, Zuhair; Aslam, Nazia; Iqbal, Naeem; Hussain, Syed Sarfaraz; Usman, Muhammad; Abbas, Mubashir; Tahir, Muhammad; Abbas, Sammar; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomaterials (NMs) are the leading edge as an amazing class of materials that consists of at least one dimension in the range of 1 to 100 nm. NMs can be made with exceptional magnetic, electrical and catalytic properties different from their bulk counterparts. We summarized unique features of NMs, their synthesis and advances in agri-nanotechnology and cutting-edge nano-bionics. The review describes advances in NMs including their applications, dosimetry to ensure biosafety, remote sensing of agro-forestry fields, nano-fertilizers, nano-pesticides, avoid post-harvest losses, gene delivery and nano-bionics. Tree-nanobionics has enabled synthesis and delivery of nano-sensors which enhance rate of photosynthesis, detection of pathogens and poisonous residues to ensure biosafety and biomass accumulation. Finally, we conclude by discussing challenges, future perspectives, and agro-ecological risks of using NMs.